Study on the Cracking Mechanism of YQ450NQR1 High-Strength Weathering Steel - Qing, J.S.; Duan, X.D.; Xiao, M.F.; Li, J.Q.; Liu, M.; Liu, Q.; Shen, H.F. (Проблемы прочности, 2018)
YQ450NQR1 high-strength weathering steel is prone to cracking. The cracking patterns and morphology were detected by metallographic and scanning electron microscopies. The decarburized layer around the cracks is indicative of their origination in the continuous casting bloom. Then, the controlling factors were established by analyzing the carbon content of molten steel, residual elements in the alloy, purity and performance of the mold powder, and secondary cooling water flow of the mold. Results show that the process optimization reduced the cracking reject ratio from 3.5 to 0.78%.